2022
DOI: 10.1038/s41598-022-27028-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular surveillance of arboviruses circulation and co-infection during a large chikungunya virus outbreak in Thailand, October 2018 to February 2020

Abstract: A large national outbreak of chikungunya virus (CHIKV) was recently reported in Thailand. While dengue virus (DENV) infection tends to occur year-round with an upsurge in the rainy season, Zika virus (ZIKV) also circulates in the country. The overlap in the distribution of these viruses increased the probability of co-infections during the heightened CHIKV activity. By examining 1806 patient serum samples submitted for CHIKV diagnostics from October 2018-February 2020 (511 CHIKV-negatives and 1295 CHIKV-positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 61 publications
1
10
0
2
Order By: Relevance
“…The female gender was associated with a higher risk of symptomatic chikungunya. Similar results were observed during outbreaks in India and Thailand 3,13 . It is possible that sex hormones might modulate the inflammatory response, contributing to the development of symptomatic disease 14 .…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…The female gender was associated with a higher risk of symptomatic chikungunya. Similar results were observed during outbreaks in India and Thailand 3,13 . It is possible that sex hormones might modulate the inflammatory response, contributing to the development of symptomatic disease 14 .…”
Section: Discussionsupporting
confidence: 75%
“…Age above 30 has been reported to be associated with symptomatic chikungunya 3 . A study from Thailand has shown that higher age was associated with the presence of joint pain in CHIKV‐infected subjects 13 . The female gender was associated with a higher risk of symptomatic chikungunya.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2006, Kolkata, West Bengal, India, experienced a CHIKV out-break. Even though a few occasional cases of CHIKV infection were investigated from a few Indian states between 2010 and 2015 [ 3 ], the rate of infection has been declining until a 2016 outbreak in the capital city Delhi [ 4 ]. Currently, the disease has spread throughout the entire nation and outbreaks cause significant economic and productivity losses.…”
Section: Introductionmentioning
confidence: 99%